Pola Kalimat Inversi Deklaratif pada Lirik Lagu Mahalini Raharja Tahun 2024: Kajian Sintaksis - Alfiana, Fitri Alaida; Suhartono, Suhartono (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2024)
In this research, use of declarative inversion sentence patterns in the lyrics of song Mahalini Raharja 2024 was analyzed. The aim of this research was to identify and describe pattern of declarative inversion sentences in the lyrics of the song Mahalini Raharja 2024 based on syntax theory. Descriptive qualitative methods are applied to obtain in-depth, critical, logical and holistic research results. Data collection techniques in this research are literature studies and descriptive analysis studies. The research data source was obtained from the lyrics of the song Mahalini Raharja which was released in 2024. In this research, findings are presented which describe twenty sentences declarative inversion of pattern in the lyrics of song Mahalini Raharja in year 2024, including of (1) eight sentences were found to have a declarative inversion pattern in the lyrics of the song bermuara, (2) seven sentences were found to have a declarative inversion pattern in the lyrics of the song mati-matian, and (3) five sentences were found to have an inversion pattern declarative in the lyrics of the song sampai menutup mata mahalini's version. By observing the lyrics of the song Mahalini Raharja, declarative inversion sentences can be characterized by predicate being positioned before subject at the beginning of the sentence. Based on the results analysis, it can be concluded that declarative inversion sentence pattern in the lyrics of the song Mahalini Raharja consists of: P-S, P-K, P-S-O, P-S-K, P-S-Pel, K-P-S, and P-S-P. The interesting element of this research is discussion of declarative inversion sentence patterns in a sentence structure that is different from normal sentences because of inversion structure as a feature and role in declaring meaningful information in sentence. Urgency of this research is the use declarative inversion sentences to make sentences more effective, but not scientifically logical.